GAS ABRASIVE WEAR OF NICKEL-BASED HEAT-RELATIVE ALLOYS - Кудрін, А. П.; Лабунець, В. Ф.; Кучеренко, В. О.; Хижко, В. Д. (Proceedings of National Aviation University (archive), 2021)
The technique and installation for research of gas-abrasive wear of heat-resistant alloys on the basis of nickel are resulted. The processes that develop on the working surfaces of alloys are determined. Recommendations for the restoration of worn blades of gas turbine engines made of heat-resistant nickel alloys are offered.